PendampinganTata Kelola Keuangan, Aset dan Pajak Tiga Desa di Kabupaten Bogor - Soffan Marsus; Andykha David Novri Sitanggang; Ajar Parama Adhi; I Wayan Mardhana (Universitas Serang Raya, 2019)
This community service activity aims to evaluate the use of the village financial system application, the implementation of tax obligations for village treasurers and administration of village assets in Cibereum Village, Sukamaju Village, and Cipayung Datar Village in Bogor Regency. This activity involves students in the student work program. The results of the service activities obtained results that the Cibereum Village and Cipayung Datar Village had implemented this application well. From the aspect of village taxation, the main obstacle faced by the three villages above is understanding reporting obligations. Especially for Sukamaju Village, it found that there were difficulties in making e-billing for paying taxes. The Cibereum and Cipayung Datar Villages already understand the mechanism of e-billing. From the aspect of managing village assets, Sukamaju Village documents very well the evidence of asset ownership. Cipayung Datar village has used Inventory Working Paper (KKI) by the applicable laws and regulations. Cibereum Village has also recorded very well even though it is not entirely by the specified format.